Viability of lactic acid bacteria and sensory evaluation in cinnamomum verum and allium sativum-bio-yogurts made from camel and cow milk - Shori, A.B.; Baba, A.S. (2012)
The present study investigate the effect of herbal water extract prepared from Allium sativum and Cinnamomum verum on the viability of lactic acid bacteria (Lactobacillus spp and Streptococcus thermophilus) in cow- and camel-milk yogurts during 21 day refrigerated storage. The organoleptic properties of fresh-yogurts were evaluated. Lactobacillus spp count for fresh cow milk-yogurts (0 day) in both present and absent of C. verum and A. sativum was ranged from 1.4×0 6 to 2.1×10 6 cfu/mL. These values were not significantly changed throughout the 21 days of refrigerated storage. Lactobacillusspp count in fresh plain camel milk- yogurt was 13.2×10 6 cfu/mL whereas fresh C. verum- and A. sativum-camel milk- yogurts had higher Lactobacillusspp counts (19.2×10 6 and 26.9×10 6 cfu/mL respectively; p<0.05). However, refrigerated storage to 21 days resulted in linear decrease in Lactobacillusspp counts. Furthermore, S. thermophilus counts in fresh cow- and camel- milk yogurts in either absent or present of C. verum or A. sativum ranged from 2.4 to 3.6×10 8cfu/mL and these values increased by day 14 of storage. In organoleptic properties of yogurts no differences were observed in sourness, bitterness, and overall preference scores between the two groups of yogurts. The present of A. sativum in cow milk-yogurt reduced the aroma score to (2.3±0.7, p<0.05) compared to camel milk-yogurt (5.5±1.0). © 2011 .